2021
DOI: 10.3390/nano11071691
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Encapsulated Chitosan-Cellulose Fiber Bionanocomposites: Synthesis, Characterization and In Vitro Analysis towards Colorectal Cancer Cells

Abstract: Cellulose and chitosan with remarkable biocompatibility and sophisticated physiochemical characteristics can be a new dawn to the advanced drug nano-carriers in cancer treatment. This study aims to synthesize layer-by-layer bionanocomposites from chitosan and rice straw cellulose encapsulated 5-Fluorouracil (CS-CF/5FU BNCs) using the ionic gelation method and the sodium tripolyphosphate (TPP) cross-linker. Data from X-ray and Fourier-transform infrared spectroscopy showed successful preparation of CS-CF/5FU BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…With adjusting the crosslinking degree of TPP and LMWC to synthesize ChNPs, improved properties of the NPs can be obtained for various applications. The optimized ratio between the LMWC to TPP cross-linker was 1:2 (v/v) as stated in our previous study [9]. Also, a separate study [8] used this ratio between TPP and chitosan, along with 1.0% acetic acid, and 2% (v/v) Tween-80 in the chitosan solution to synthesize ChNPs with suitable physiochemical characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With adjusting the crosslinking degree of TPP and LMWC to synthesize ChNPs, improved properties of the NPs can be obtained for various applications. The optimized ratio between the LMWC to TPP cross-linker was 1:2 (v/v) as stated in our previous study [9]. Also, a separate study [8] used this ratio between TPP and chitosan, along with 1.0% acetic acid, and 2% (v/v) Tween-80 in the chitosan solution to synthesize ChNPs with suitable physiochemical characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…It is the most important derivative of chitin obtained from the shells of insects and crustacean such as prawns or crabs, as well as the cell walls of fungi [8]. Many studies have used chitosan and various cross-linker to fabricate chitosan-based NPs with high biocompatibility, nontoxicity, biodegradability, and colloidal stability [8,9]. Ionic gelation, reverse micellar method, emulsification solvent diffusion are the popular method for fabrication of ChNPs [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that NPs in different geometries could interact with cell membranes differently and might exert different biological activities. With the advent of nanotechnology, modifications can be made on native cellulose fibers to manufacture nano-celluloses including cellulose nanowhiskers (CNWs), nanocrystals and nanofibers [105][106][107][108][109]. The rod-like CNWs are believed to be a promising DDS owing to their nano-dimensions, large surface area, hydrophilic properties, and high biocompatibility and biodegradability [110].…”
Section: Shape Of Nanoparticlesmentioning
confidence: 99%